2001
DOI: 10.1080/10715760100301321
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxo-7,8-dihydroguanine and 8-oxo-7,8-dihydro-2′-deoxyguanosine levels in human urine do not depend on diet

Abstract: In the present study, we used the method involving HPLC pre-purification followed by gas chromatography with isotope dilution mass spectrometric detection for the determination of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodGuo) and 8-oxo-7,8-dihydroguanine (8-oxoGua) in human urine. The mean levels of 8-oxoGua and 8-oxodGuo in the urine samples of the subjects on unrestricted diet were respectively 1.87 nmol/kg 24 h (+/-0.90) and 0.83 nmol/kg 24 h (+/-0.49), and in the case of the groups studied, they did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…Other factors, such as cell death and diets, might contribute to increase urinary 8-oxodG levels. However, the evidence was limited (36,37). Although genetic background (such as DNA repair capability) from each participant could confound the estimated effect, two measurements on the consecutive days in the present study could minimize these effects.…”
Section: Discussionmentioning
confidence: 83%
“…Other factors, such as cell death and diets, might contribute to increase urinary 8-oxodG levels. However, the evidence was limited (36,37). Although genetic background (such as DNA repair capability) from each participant could confound the estimated effect, two measurements on the consecutive days in the present study could minimize these effects.…”
Section: Discussionmentioning
confidence: 83%
“…As with previous studies (75), the authors could only presume that the isotopically labeled DNA components/adducts pass through the gastrointestinal tract to appear in feces. Nevertheless, these results, coupled with the findings of Gackowski et al (87), provide the most compelling argument that diet is not a significant contributor to both urinary 8-oxoGua and 8-oxodG levels in human urine. This is consistent with the animal data relating to 2 ¶-deoxyribonucleoside lesions (75), which includes thymidine glycol (23), but disagrees with early data for 8-oxoGua and thymine glycol (23,89).…”
Section: Sources Of Extracellular Oxidatively Modified Dna Lesionsmentioning
confidence: 79%
“…Reardon et al (28) showed the removal of 8-oxodG by NER. A recent study suggests that NER represents a plausible mechanism by which 8-oxodG and oligomers containing 8-oxodG appear extracellularly in cell culture supernatant, plasma, or urine (29). XPA was previously reported to be actively involved in the dual incision step of repairing ROS-induced 5V,8-purine cyclodeoxynucleosides, which is formed by intramolecular cross-linking between the C-8 position of adenine or guanine and the 5V position of 2-deoxyribose (30).…”
Section: Discussionmentioning
confidence: 99%